PERAN WORLD HEALTH ORGANIZATION (WHO) DALAM MENANGANI WABAH KOLERA DI MALAWI PERIODE 2022-2023 - Amalia, Nisa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The World Health Organization (WHO) is the largest health organization that helps address health problems in the world by providing direction, assistance in the form of health facilities, logistics, funds, and working with the community to fight health problems in the world. Malawi experienced the worst cholera outbreak in its history with 59,156 cases in 2022-2023. In this context, WHO is playing a crucial role in helping Malawi to deal with the cholera outbreak during this period. The results of this study indicate that the World Health Organization has played an important role in addressing the cholera outbreak in Malawi. Based on the theory of International Organizations proposed by Clive Archer, international organizations can act as instruments, arenas, and independent actors. As an instrument, WHO supports the Malawian government to conduct socialization, campaigns, monitoring and supervision and vaccination. As an arena, WHO acts in organizing coordination meetings with the Malawian government. As an independent actor, WHO provides operational assistance, logistics, funds, and sends health workers to treatment centers. Keywords: World Health Organization (WHO), Malawi, Cholera, Health